PEMANFAATAN DAUN KELAKAI SEBAGAI BAHAN AKTIF GEL MOISTURIZER HERBAL ANTI-UV UNTUK PENINGKATAN NILAI EKONOMI TANAMAN LOKAL - Sembiring, Pintata (Jurnal Pengabdian Masyarakat Putri Hijau, 2026)
Exposure to ultraviolet (UV) radiation is one of the main factors causing skin damage such as premature aging, hyperpigmentation, and skin irritation. The use of natural ingredients as skin protection agents is a safer and more environmentally friendly alternative. Kelakai leaves (Stenochlaena palustris) are a local plant known to contain flavonoids and antioxidants that have the potential to be used as active ingredients in herbal anti-UV cosmetics. This community service activity aims to increase public knowledge about the use of local plants and develop herbal anti-UV moisturizing gel products based on kelakai leaf ethanol extract. The activity methods include the formulation of moisturizing gel preparations, testing of physical stability and Sun Protection Factor (SPF) values, counseling, product manufacturing training, and evaluation of increased public knowledge through pre-test and post-test methods. The results of the activity showed that the gel formulation had good physical stability and an SPF value in the moderate to high protection category. The educational sessions increased the community's understanding of the use of local plants as products with economic value. This program demonstrated that kelakai leaves have the potential to be developed into herbal cosmetic products based on local wisdom.